Designing Web interfaces - Scott, Bill.; Neil, Theresa (Beijing ; Cambridge [MA] : O$1 (BReilly, s, 2009)
If you want to learn how to create great user experiences on the Web, this practical book offers more than 75 design patterns for building interfaces that provide rich interaction. Distilled by two longtime professionals after years of experience at Sabre, Yahoo, and Netflix, these design patterns and best practices are neatly organized according to six key principles that help you take advantage of current interactive web technologies -- With the recent advent of Ajax and the resurgence of Flash for developing web sites and applications, new patterns of interaction have emerged on the Web. In this book, Bill Scott provides insight on how to best take advantage of the power of these technologies for designing a great user experience through a series of best practices, summarized as eight key principles. Each principle and its nuances are illustrated in detail with real world examples and counter-examples from both inside and outside Yahoo! The design principles provide the rationale for how to apply a pattern. Design patterns provide a solution in context. The eight design principles are introduced as a set of principles focused on rich interaction, feedback and user data models. Benefits to reader: 1. Take-away the key principles for creating a rich experience on the web 2. Build a vocabulary around common patterns of interaction for a common language between engineering & design 3. Have numerous real-world examples to clearly understand the principles & patterns for future reference 4. Be able to apply the patterns & principles in real world design problems Includes a companion website: designingrichwebexperience.com
In-Page Editing -- Drag and Drop -- Direct Selection -- Contextual Tools -- Overlays -- Inlays -- Virtual Pages -- Process Flow -- Static Invitations -- Dynamic Invitations -- Transitional Patterns -- Purpose of Transitions -- Lookup Patterns -- Feedback Patterns.
Includes bibliographical references and index.
1
Keywords: Dynamic Invitations; Static Invitations; Inlays; Contextual Tools; Drag and Drop; User interfaces (Computer systems) -- Design; Interfaces utilisateurs (Informatique) -- Conception